Locomotor activity in Aedes aegypti with different insecticide resistance profiles - Bruno Magalhães Nakazato; Maria de Lourdes da Graça Macoris; Paulo Roberto Urbinatti; Tamara Nunes Lima-Camara (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To evaluate locomotor activity in four field populations of Ae. aegypti with different insecticide resistance profiles from the state of São Paulo for two years. METHODS: This study comprised the susceptible Rockefeller strain and four populations from São Paulo, Brazil: two considered populations with "reduced susceptibility" to pyrethroids (Campinas and Marília), and two "resistant populations" (Santos and Ribeirão Preto). First, 2016 and 2017 eggs from these five populations were hatched in laboratory. Virgin females underwent experiments under laboratory conditions at 25°C, with 12:12h light/dark (LD) photoperiod; 24-hour individual activity was recorded using a locomotor activity monitor (LAM). RESULTS: In females from 2016 field populations, both resistant populations showed significant more locomotor activity than the two reduced susceptibility populations and the Rockefeller strain (p < 0.05). As for females from 2017 field populations, reduced susceptibility populations showed a significant increased locomotor activity than the Rockefeller strain, but no significant difference when compared to Santos resistant population (p > 0.05). CONCLUSIONS: Our results indicate that insecticide-resistant Ae. aegypti populations show increased locomotor activity, which may affect the transmission dynamics of their arboviruses.